Εἶδος e ἰδέα: das origens da literatura grega aos primeiros diálogos de Platão - Moreira, Julio Cesar (2019)
The aim of this investigation is to determine the historical semantic content that Plato inherits from the words εἶδος and ἰδέα and the ways he initially employs this heritage in the development of his philosophy. These terms are still a matter of dispute among the most reputable scholars on Plato’s thought, especially in respect to the philosophy of Forms. In this sense, regarding Plato’s early dialogues, currently the main debate among scholars is between a developmentalist or unitarian approach to the philosophy of Forms. Another debate, among many issues, is whether the philosophical use of these words in the early dialogues are indeed a Platonic novelty. In addition to the philosophical use, Plato does not cease to employ many of the semantic aspects already inherent in both words, which are also not free of disputes about them. Seeking to shed more light on the previously mentioned and other related issues, we propose a study of the words εἶδος and ἰδέα from their origins in Greek literature to the Plato’s so-called early dialogues. First, we develop a diachronic study of the general philological and semantic aspects of εἶδος and ἰδέα from their first appearances in Greek literature to the fragments of the Presocratic philosophers, outlining the semantic development of the words as Plato would later inherit them. Then, we address Socrates and the issue of how to properly approach his philosophy and historical figure. Finally, we analyze this vocabulary of forms in Plato's early dialogues, giving the philosophical analysis methodological priority over philological analysis. We argue that Socrates never used εἶδος and ἰδέα in relation to his question “τί ἐστι X?” and that the inclusion of this vocabulary in this Socratic inquiry would thus be an addition by Plato. Furthermore, we distinguish, in the early works of Plato, all the commonly used meanings of the words while verifying to what extent Plato is consistent or different in the way he employs them when compared to the usage of the words in previous literary fields. Regarding the philosophy of Forms, our results are in line with the unitarian theory